Politisation du pouvoir judiciaire et judiciarisation du pouvoir politique : la séparation traditionnelle des pouvoirs a-t-elle vécu ? - Brun, Henri; Lemieux, Denis (Les Cahiers de droit, 1977)
Emphasis has recently been placed on the danger of governmental agencies moving in the direction of what may be termed "judiciallisation", as a result of the growing tendency of the government to become involved in adjudication. Meanwhile, very little attention has been given to the independence of the judiciary, the watchdog over the governmental processes. On the one hand, professors Brun and Lemieux realize that the prerequisites of the independence of some governmental activities are just maintained and that the Courts have adapted different tests to different type functions. On the other hand, they realize that the independence of the judiciary is at the same time more and more endangered. Government designations of judges, interventions in, and associations with, the judiciary may convince many people that the latter is but a branch of the former. Moreover, the Courts themselves generally show too dormant an attitude in this area.